POSH / Farisa Dania Mat Zahid - Mat Zahid, Farisa Dania (2020)
POSH is a company founded by a lifestyle disruptor aiming to bring in innovative mugs that will improve and better everyone’s lifestyle. The name POSH is chosen because the word itself means elegant and stylish which perfectly represents the product that we produce. POSH came up with its first innovative product, THATmug which is a self-stirring and non-tippable mug which concept highly promotes convenience and security to its users due to its unique features. The idea of this mug came the founder of the company, Farisa Dania binti Mat Zahid while she was observing a single mother in a park struggling to make her own coffee and taking care of her baby at the same time. With technological advancements, POSH desires to solve the problems that one faces when using a regular mug and add a fancy touch on it. POSH also believes in getting the perfect gift for any kind of occasion hence it provides a packaging in presentable gift boxes made of 100% recycled item